The role of the learning environment in addressing online learning in the Covid-19 era - Galuh Asprilia Fadhilah (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2020)
Since the outbreak of the Corona Virus Disease pandemic (covid-19) has had a significant impact on all aspects of life, especially education. In the world of online learning education is considered to be a new thing in the process so that many students and teachers feel strange doing it. The number of obstacles experienced make online learning not yet implemented well. The lack of preparation for the role of the learning environment is considered to be a contributing factor to online learning in the Covid 19 era. The purpose of writing this article are 1) Describe the role of the environment in the mathematics learning process of elementary school students in the Covid-19 era. 2) Analyzing the impact arising from the unpreparedness of the learning environment in implementing online learning in the Covid-19 era. This research method uses the type of literature study. The object of this research focuses on the role of the learning environment in addressing online learning in the Covid era 19. The validity of the data is done by triangulating various sources. The data analysis technique used in this study is the Constant Comparison method. The results of this study are 1). The learning environment plays an important role in implementing online learning. 2). Online learning takes place suddenly so that the lack of preparation of the learning environment is the main problem at hand. That causes many obstacles faced in implementing online learning.